2019
DOI: 10.3844/ojbsci.2019.51.56
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Approach to Identify Gobioid Fishes, “Nike” and “Hundala” (Local Name), from Gorontalo Waters, Indonesia

Abstract: Data of the species scientific name is required to study biodiversity and conservation of local fish species. Nike and hundala are the local names for fish found in Gorontalo whose scientific names are unknown and recognized by local people as two different species of fish. This study aims to identify the genetic and species of nike and hundala fish. Nike and hundala specimens were collected using a fish net from the estuary of Gorontalo Bay and Bone River, Gorontalo, Indonesia in April 2018. Molecular analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…S. parvei Bleeker 1853, S. cynocephalus, S. longifilis, S. lagocephalus, and Stiphodon semoni) from the Gobiidae family; and Belobranchus belobranchus Valenciennes 1837 from the Eleotridae family. One species, S. longifilis, is the same species as reported by Olii et al (2019) without a description of specific melanophore patterns, and one species, S. cynocephalus, is also the same species with a different melanophore pattern as reported by Sahami et al (2019b). The results of molecular analysis were able to identify the samples up to the species level and further clarify the results of morphometric analysis.…”
Section: Molecular Analysissupporting
confidence: 52%
See 2 more Smart Citations
“…S. parvei Bleeker 1853, S. cynocephalus, S. longifilis, S. lagocephalus, and Stiphodon semoni) from the Gobiidae family; and Belobranchus belobranchus Valenciennes 1837 from the Eleotridae family. One species, S. longifilis, is the same species as reported by Olii et al (2019) without a description of specific melanophore patterns, and one species, S. cynocephalus, is also the same species with a different melanophore pattern as reported by Sahami et al (2019b). The results of molecular analysis were able to identify the samples up to the species level and further clarify the results of morphometric analysis.…”
Section: Molecular Analysissupporting
confidence: 52%
“…The sampled fishes were temporarily preserved in an icebox (4 °C) and were transported to the laboratory for further analysis. The morphology of the Nike fish is recognized by the morphological features described by Olii et al (2019) and Pasisingi et al (2020a). The sample grouping referred to the initial method used by based on the differences in melanophore patterns in the body.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gani et al (2019) found Sicyopterus lagocephalus and S. longifilis in Biak and Koyoan River, Central Sulawesi. S. longifilis and S. pugnans were also identified by Olii et al (2019) in Gorontalo Bay and Bone River, Gorontalo waters. A total of 96 individuals of Sicyopterus species found by Nurjirana et al (2019), including Sicyopterus lagocephalus, S. longifilis, and Sicyopus zosterophorum in Leppangan River, West Sulawesi.…”
Section: Discussionmentioning
confidence: 88%
“…Mitochondrial cytochrome oxidase subunit I (COI) gene could serve as a rapid and reliable barcoding marker for identifying species and effective in delimitating species of various animals (Hebert et al 2004;Hubert et al 2008;Imtiaz et al 2017;Roesma et al 2018;Roesma et al 2019). Recently, the COI gene has been widely used to resolve the taxonomy in a gobioid group (Jeon et al 2012;Jin et al 2014;Taillebois et al 2014;Wang et al 2017;Olii et al 2019). Further research is needed on Rinuak and Badar fish using a molecular approach.…”
Section: Introductionmentioning
confidence: 99%